Law Enforcement Against Perpetrators Of Physical Sexual Violence Against People With Mental Disorders (ODGJ) - Atika, Dea Silmi; Monica , Dona Raisa; Farid , Muhammad (Multidisciplinary Journals, 2025)
The crime of physical sexual violence against individuals with mental disorders is a serious human rights violation and requires strict law enforcement. This study examines Decision Number 657/Pid.B/2024/PN Tjk, in which the defendant was found guilty under Article 285 of the Criminal Code and sentenced to eight years in prison and a fine of Rp 2,000. This study aims to analyze how law enforcement is carried out against perpetrators of sexual violence targeting people with mental disorders and to identify factors that hinder this process. Using a normative and empirical juridical approach, data were collected through a literature review and interviews with investigators, judges, and legal scholars, then analyzed qualitatively. The findings indicate that although law enforcement has been carried out in accordance with the Criminal Code, weaknesses still remain, especially at the execution stage, which focuses more on punishment than on victim recovery. In addition, this study identifies challenges related to legal substance, law enforcement capacity, infrastructure, and socio-cultural attitudes. In conclusion, synchronization between the Criminal Code and Law Number 12 of 2022 concerning Crimes of Sexual Violence is crucial to ensure justice, with an emphasis on victim restitution, rehabilitation, and strengthening inter-institutional coordination.